All Days 2016
DOI: 10.2118/184348-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Rena and Mycoremediation Techniques in Reduction of Heavy Metals in Crude Oil Impacted Soil

Abstract: The comparative study of RENA, Mycoremediation and combination of the two techniques were carried out to determine their ability in the degradation of selected heavy metals (Cadmium, Chromium, Nickel, lead, Zinc, Manganese and Iron) in a Crude oil impacted soil. Three different plots for each technique and control were each spiked with 7.5 Litres of Bonny Light crude Soil Samples were taken at 0-15cm and 15-30cm depths for each of the techniques and control at 0, 4, 8, 12, 16 and 20 weekly intervals for heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…At the laboratory level, composting with farmyard manure and poultry droppings, bioaugmentation using two strains of bacteria (Pseudomonas aeruginosa and Bacillus subtilis), and mycoremediation using white-rot fungus (Pleurotus ostreatus) have been applied in the bioremediation of drill cuttings . However, it has been suggested that field-scale treatment of drill cuttings by RENA whether in biopiles or windrows has the potential to pollute local groundwater sources and faces limited land availability challenges because of large-space requirement Maduekwe et al, 2016). Similarly, bioaugmentation has been reported to have huge field-scale adaptability challenges (KMC Oiltools, 2005), which include: (1) overarching issue of the ability of the laboratory-prepared microbes to adapt to field conditions; (2) requirement of large volume of biopreparation of microbial consortium for use in the field; and (3) associated huge financial burden.…”
Section: Biological Methodsmentioning
confidence: 99%
“…At the laboratory level, composting with farmyard manure and poultry droppings, bioaugmentation using two strains of bacteria (Pseudomonas aeruginosa and Bacillus subtilis), and mycoremediation using white-rot fungus (Pleurotus ostreatus) have been applied in the bioremediation of drill cuttings . However, it has been suggested that field-scale treatment of drill cuttings by RENA whether in biopiles or windrows has the potential to pollute local groundwater sources and faces limited land availability challenges because of large-space requirement Maduekwe et al, 2016). Similarly, bioaugmentation has been reported to have huge field-scale adaptability challenges (KMC Oiltools, 2005), which include: (1) overarching issue of the ability of the laboratory-prepared microbes to adapt to field conditions; (2) requirement of large volume of biopreparation of microbial consortium for use in the field; and (3) associated huge financial burden.…”
Section: Biological Methodsmentioning
confidence: 99%